Teologi Satu Tubuh dari Perspektif Pluralisme: Kajian Historis Kritis Kolose 3: 11 – 17 dan Implikasinya - Yois Fabeat; Monike Hukubun (Program Pascasarjana UKIM, 2022)
Pluralism is a reality in people's lives in Indonesia and Moluccas. In this regard, the exclusive notions that are built up in religious life also contribute to the creation of conflicts that threaten the integrity of a pluralistic society. Therefore, it needs to be actively addressed by the church. One way is to make efforts to interpret the biblical text in this case the text of Colossians 3:11-17. This article is the result of an interpretation using the historical criticism method on the text of Colossians 3:11-17. In the interpretation, it is found that the text of Colossians 3:11-17 contains a theological understanding of plurality values. Pluralism is then understood as a theological truth, where Jesus bridges all differences without ignoring the unique identity of each individual and group. So that everyone is seen as the same in different functions which are analogous to